“Color azurei obscurissimi”. Kabbalistic hues in ‘Azriel of Gerona and Flavius Mithridates (Itinera, 2020)
The general topic of Colours and their symbolic significance in Kabbalah has been presented by Gershom Scholem in a well-known conference at Eranos. The present article concentrates on the quite eccentric representation of colours and their association to the ten Sefirot in the Sha’ar ha-Sho’el of ‘Azriel of Gerona, one the early Kabbalists who lived in Catalunya in the 13th century. Since the Sha‘ar ha-Sho’el, an introduction to the basic tenets of Kabbalah in the form of a philosophical dialogue, has been translated into Latin in 1486 by the converted Jew Flavius Mithridates for Giovanni Pico della Mirandola, the translation is used as a reflection of the Hebrew original in order to analyze the chromatic denominations chosen by the translator in order to render a mental picture of the colours he found described in the text with the additional difficulty that some of the colours mentioned by ‘Azriel are not univocally understood in Jewish tradition. The elusive character of colours in general is here perceived through the glass of a transcultural and transreligious linguistic rendering which, in the best event, can help interpret the original, and in the worse, can lead us to appreciate the difficulty of the task and its intrinsic reasons.